Performance following prolonged sub-maximal cycling at optimal versus freely chosen pedal rate - Hansen, E. A.; Jensen, K.; Pedersen, P. K. (European Journal of Applied Physiology, 2006)
It was tested whether cyclists perform better during all-out cycling following prolonged cycling at the pedal rate resulting in minimum oxygen uptake (VO2), i.e. the energetically optimal pedal rate (OPR) rather than at the freely chosen pedal rate (FCPR). Nine trained cyclists cycled at 180W to determine individual OPR and FCPR. Baseline performance was determined by measuring mean power output (W5min) and peak VO2 during 5-min all-out cycling at FCPR. Subsequently, on two separate days, the cyclists cycled 2.5 h at 180 W at OPR and FCPR, with each bout followed by a 5-min all-out trial. FCPR was higher (P < 0.05) than OPR at 180W (95 § 7 and 73 § 11 rpm, respectively). During the prolonged cycling, VO2, heart rate (HR), and rate of perceived exertion (RPE) were 7-9% higher (P < 0.05) at FCPR than at OPR and increased (P < 0.05) 2-21% over time. During all-out cycling following prolonged cycling at OPR and FCPR, W5min was 8 and 10% lower (P < 0.05) than at baseline, respectively. Peak VO2 was lower (P < 0.05) than at baseline only after FCPR. The all-out trial power output was reduced following 2.5 h of cycling at 180W at both OPR and FCPR. However, this aspect of performance was similar between the two pedal rates, despite a higher physiological load (i.e. VO2, HR, and RPE) at FCPR during prolonged cycling. Still, a reduced peak VO2 only occurred after cycling at FCPR. Therefore, during prolonged sub-maximal cycling, OPR is at least as advantageous as FCPR for performance optimzation in subsequent all-out cycling.